Characterization of Myosatellite Stem Cells from Black Bone Chicken and Effect of Different Animal Serums on Growth Performance - Chaiyod, Rungravee; Lertworapreecha, Monthon (Trends in Sciences, 2024)
Isolation of muscle stem cells (myosatellite stem cells) of black bone chickens using enzymatic digestion, the pronase, and screening by low-speed centrifugation process combined with 40 μm cell strainer filtration showed that this method was able to separate chicken muscle stem cells efficiently. The results proved that the isolated cells were myosatellite stem cells expressing marker genes, c-met, Pax7, MyoD, and myogenin, by RT-PCR assay. Additionally, immunofluorescence staining with monoclonal antibodies confirmed the isolated cells were MSCs, with positive staining for canonical markers proteins: Pax7, Desmin, and actin. Evaluating the influence of fetal bovine serum (FBS), horse serum (HS), and chicken serum (CKS) supplements on MSC proliferation revealed that FBS emerged as the most effective despite its escalating cost and emerging need for alternatives. Notably, Chicken Serum (CKS) demonstrated potential as an alternative, closely following the cell proliferation rate achieved by FBS. Our findings affirm the efficacy of the devised isolation method and highlight the potential of using chicken serum in cell culture protocols. HIGHLIGHTS This research established a technique for isolating myosatellite stem cells from black bone chickens through enzymatic processes combined with gradient methods. Centrifugation aids in obtaining a purer isolation of these stem cells and allows for the evaluation of various animal serums’ effects. In cell cultures, the performance of chicken serum showed no significant difference compared to bovine serum. GRAPHICAL ABSTRACT